2012
DOI: 10.1515/jpem-2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

Is vitamin D deficiency a feature of pediatric celiac disease?

Abstract: Background: Celiac disease (CD) is an autoimmune enteropathy characterized by villus atrophy and malabsorption of essential nutrients. Vitamin D defi ciency has been described in autoimmune diseases, but its status in prepubertal children with CD has not been adequately studied. Objective: To determine the vitamin D status of prepubertal children with CD. Study design: A retrospective study of prepubertal children aged 3 -12 years with CD (n = 24) who were compared to prepubertal, non-CD children of the same a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
4
17
1
Order By: Relevance
“…When associating the plasma 25(OH)D concentration with the nutritional status in our study, the insufficient and deficient parameter were concentrated in the group with normal nutritional status (nine cases, 56.2%). However, no statistically significant differences were found, contrary to what was reported in the Villanueva study, where CD children with obesity showed lower 25(OH)D concentrations, compared with eutrophic children (8). These findings are consistent with other studies that report that the higher obesity prevalence, the lower the 25(OH)D concentrations compared to healthy, non-obese children.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…When associating the plasma 25(OH)D concentration with the nutritional status in our study, the insufficient and deficient parameter were concentrated in the group with normal nutritional status (nine cases, 56.2%). However, no statistically significant differences were found, contrary to what was reported in the Villanueva study, where CD children with obesity showed lower 25(OH)D concentrations, compared with eutrophic children (8). These findings are consistent with other studies that report that the higher obesity prevalence, the lower the 25(OH)D concentrations compared to healthy, non-obese children.…”
Section: Discussionsupporting
confidence: 80%
“…According to this finding, there was no evidence of vit D deficiency in the pediatric population with CD 1 . A possible explanation is that the vit D deficiency in children and adults with CD would not depend exclusively on its gastrointestinal absorption, but also on the endogenous production of it, specially vitamin D3, which is formed from the exposure of 7-dehydrocholesterol in the skin through the solar ultraviolet-B rays transforming it into previtamin D3 8 .…”
Section: Introductionmentioning
confidence: 99%
“…involving 141 patients of all ages with CF over a period of four years demonstrated that the amount of sunlight exposure, but not even an oral supplementation of up to 800 IU vitamin D/day, was the key determinant to the serum vitamin D level in these patients . Similarly, studies of children demonstrated that when children with CD and Crohn's disease had as much sunlight exposure or outdoor activity as that of healthy children, there was generally no significant difference in the serum vitamin D levels between these two groups …”
Section: Insufficient Sunlight Exposure Is a Significant Factor For Vmentioning
confidence: 99%
“…If one looks in younger populations one sees a different result. For example, Villanueva et al, found marginally higher 25-hydroxy vitamin D levels among children with celiac than among controls but the difference seemed to be associated with differences in body mass [91]. Second, Bickle has suggested that elevated 1,25-dihydroxy vitamin D may be common in celiac disease [92].…”
Section: Two Counter Arguments Examinedmentioning
confidence: 99%